ENHANCING QUALITY OF LIFE FOR INDIVIDUALS WITH INTELLECTUAL DISABILITIES: STRATEGIES AND INTERVENTIONS - Manish Kumar Meena (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
This paper explores the strategies and interventions aimed at enhancing the quality of life for individuals with intellectual disabilities (ID). Intellectual disabilities affect cognitive functioning and adaptive behaviors, leading to challenges in everyday life activities. Improving the quality of life for these individuals necessitates a holistic approach encompassing healthcare, education, social inclusion, and supportive environments. This research delves into various methodologies and their efficacy, examining case studies and current practices to provide a comprehensive overview of effective interventions.